2019
DOI: 10.1016/j.jmb.2019.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of denatured states of sensory rhodopsin II by solution-state NMR

Abstract: Sensory rhodopsin II (pSRII), a retinal-binding photophobic receptor from Natronomonas pharaonis, is a novel model system for membrane protein folding studies. Recently, the SDS-denatured states and the kinetics for reversible unfolding of pSRII have been investigated, opening the door to the first detailed characterisation of denatured states of a membrane protein by solution-state nuclear magnetic resonance (NMR) using uniformly 15 N-labelled pSRII. SDS denaturation and acid denaturation of pSRII both lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(86 reference statements)
1
2
0
Order By: Relevance
“…Moreover, order parameters of Ile and Leu tend to decrease with increasing distance to the retinal binding site (Figure S13), supporting the view that bound retinal confers conformational stability to the protein center, which is propagated by allosteric pathways to the outside of the bundle. This observation agrees with recent folding studies of sensory rhodopsin using solution NMR methods that indicated that the retinal binding region constitutes the folding core of the protein [68] . Similarly, Reat et al [69] .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, order parameters of Ile and Leu tend to decrease with increasing distance to the retinal binding site (Figure S13), supporting the view that bound retinal confers conformational stability to the protein center, which is propagated by allosteric pathways to the outside of the bundle. This observation agrees with recent folding studies of sensory rhodopsin using solution NMR methods that indicated that the retinal binding region constitutes the folding core of the protein [68] . Similarly, Reat et al [69] .…”
Section: Resultssupporting
confidence: 90%
“…The fact that we assigned the vast majority of observed peaks indicates that the missing resonances are broadened beyond detection by conformational exchange. Since the two isomeric forms that are present in the dark‐adapted state of bR interconvert too slowly to produce the observed line‐broadening, [68] we suspect that the line‐broadening is rather due to motional adaptations in the extracellular cavity of bR. We speculate that those processes might be related to the exchange of internal and bulk water [70] or the lack of stabilizing contacts in the bR monomer.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation